ANTESEDEN ORGANIZATIONAL CITIZENSHIP BEHAVIOR: STUDI PADA GURU-GURU SMA DI KOTA MADIUN - Srimulyani, Veronika Agustini (Widya Warta, 2012)
Organizational citizenship behavior (OCB) is organization member behavior that runs more effective role than the organization expected one. It plays significant roles for the company effectiveness. The purpose of this study was to examine the direct and indirect effects of transformational leadership upon organizational citizenship behaviour (OCB) mediated by work life quality and organizational commitment as the intervening variable or key antecedents. The participants comprised 165 teachers of five (5) senior high schools in Madiun.The data were collected using questionnaire, while the hypothesis was examined applying multiple regression analysis and path anaysis.The result of the path analysis indicated that transformational leadership, work life quality, and organizational commitment have a direct significant effect on organizational citizenship behavior. The model analysis indicated that transformational leadership had indirect impact on organizational citizenship behaviour (OCB, work life quality, and organizational commitment as key antecedents.